2023
DOI: 10.3390/jcm12041584
|View full text |Cite
|
Sign up to set email alerts
|

Red Blood Cell Distribution Width: A Risk Factor for Prognosis in Patients with Ischemic Cardiomyopathy after Percutaneous Coronary Intervention

Abstract: Background: It has been demonstrated in previous studies that red blood cell distribution width (RDW) is correlated with the severity and prognosis of cardiovascular disease. The target of our study was to assess the relationship between RDW and the prognosis of ischemic cardiomyopathy (ICM) patients undergoing percutaneous coronary intervention (PCI). Methods: The study retrospectively enrolled 1986 ICM patients undergoing PCI. The patients were divided into three groups by RDW tertiles. The primary endpoint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Dai et al showed that RDW was an independent predictor of MI type 4a [28]. Zhang et al showed that RDW was linked with increased risk of MACE (HR 1.75), all-cause mortality (HR 1.58), and any revascularization (HR 2.10) [29] at long-term follow-up. In the research by Wu et al, RDW was an independent predictor of cardiac death (HR 1.33) but not all-cause mortality or MACE at 3 years [30].…”
Section: Discussionmentioning
confidence: 99%
“…Dai et al showed that RDW was an independent predictor of MI type 4a [28]. Zhang et al showed that RDW was linked with increased risk of MACE (HR 1.75), all-cause mortality (HR 1.58), and any revascularization (HR 2.10) [29] at long-term follow-up. In the research by Wu et al, RDW was an independent predictor of cardiac death (HR 1.33) but not all-cause mortality or MACE at 3 years [30].…”
Section: Discussionmentioning
confidence: 99%